Phosphoproteomics: searching for a needle in a haystack - Tichy, Ales; Salovska, Barbora; Rehulka, Pavel; Klimentova, Jana; Vavrova, Jirina; Stulik, Jiri; Hernychova, Lenka (Journal of proteomics, 2011)
Most of the cellular processes are regulated by reversible phosphorylation of proteins, which in turn plays a critical role in the regulation of gene expression, cell division, signal transduction, metabolism, differentiation, and apoptosis. Mass spectrometry of phosphopeptides obtained from tryptic protein digests has become a powerful tool for characterization of phosphoproteins involved in these processes. However, there is a general need to significantly enrich the phosphopeptide content to compensate their low abundance, insufficient ionization, and suppression effects of non-phosphorylated peptides. This paper aims to give a comprehensive overview on the methods involved in recent phosphoproteomics. It presents a description of contemporary enrichment techniques with references to particular studies and compares different approaches to characterization of phosphoproteome by mass spectrometry.
Keywords: Gene Expression Regulation; fosforylace; buněčná diferenciace; Phosphorylation; fosfoproteiny; Mass Spectrometry; buněčné dělení; Phosphoproteins; proteomika; Animals; lidé; Cell Division; Humans; zvířata; regulace genové exprese; Peptides; apoptóza; peptidy; hmotnostní spektrometrie; Proteomics; Apoptosis; Cell Differentiation